2011
DOI: 10.2337/db10-1643
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Islet Interleukin-17 Pathway Activation Characterizes Human Autoimmune Diabetes and Promotes Cytokine-Mediated β-Cell Death

Abstract: OBJECTIVECD4 T-cells secreting interleukin (IL)-17 are implicated in several human autoimmune diseases, but their role in type 1 diabetes has not been defined. To address the relevance of such cells, we examined IL-17 secretion in response to β-cell autoantigens, IL-17A gene expression in islets, and the potential functional consequences of IL-17 release for β-cells.RESEARCH DESIGN AND METHODSPeripheral blood CD4 T-cell responses to β-cell autoantigens (proinsulin, insulinoma-associated protein, and GAD65 pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 37 publications
(53 reference statements)
11
174
0
3
Order By: Relevance
“…We have previously shown that IL-17A augments apoptosis in human islet cells or rat beta cells exposed to IL-1β+IFN-γ or TNF-α+INF-γ [17]. Here, these findings were expanded by the observations that IL-17A increased apoptosis induced by IL-1β+IFN-γ in rat INS-1E cells, as judged by nuclear dyes and caspase 3 cleavage (Fig.…”
Section: Il-17a Exacerbates Cytokine-induced Apoptosis In Rat Ins-1e supporting
confidence: 58%
See 4 more Smart Citations
“…We have previously shown that IL-17A augments apoptosis in human islet cells or rat beta cells exposed to IL-1β+IFN-γ or TNF-α+INF-γ [17]. Here, these findings were expanded by the observations that IL-17A increased apoptosis induced by IL-1β+IFN-γ in rat INS-1E cells, as judged by nuclear dyes and caspase 3 cleavage (Fig.…”
Section: Il-17a Exacerbates Cytokine-induced Apoptosis In Rat Ins-1e supporting
confidence: 58%
“…Recent studies indicate an increased presence of Th17 cells among circulating T cells and in the pancreatic islets of type 1 diabetes patients [16][17][18][19]. Th17 cells secrete the cytokine IL-17A, which we and others have shown to exacerbate IL-1β+IFN-γ-and TNF-α+IFN-γ-induced apoptosis in MIN6 cells and human islets [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations